Avaliação in vitro das atividades antibacteriana e citotóxica do extrato bruto e frações de Euclea natalensis frente aos agentes de infecções bucais - Lima, Danielly Davi Correia (2021)
The aim of this study was to evaluate the antibacterial and cytotoxic activities of the crude extract and fractions obtained from the roots of Euclea natalensis A.D.C against bacteria causing periodontal disease and caries, as well as to identify the isolated compounds. The minimal inhibitory concentration (MIC) and the minimal bactericidal concentration (MBC) were determined using microplate dilution assay. The cytotoxic evaluation of the extract and fractions was performed with human fibroblast cells (GM07492A, lung fibroblasts) through the XTT colorimetric assay and the elucidation of the compounds present in the most promising fraction was determined by liquid chromatography coupled mass spectrometry (HPLC-ESI-MS/MS) by means of a qualitative analysis. The MIC results ranged from 25 to >400 μg / mL for the extract and 1.56 to >400 μg / mL for the fractions. The concentrations tested for cytotoxic evaluation were 19.5 to 2500 μg / mL, with IC50 between 625 and 1250 μg / mL.The presence of pentacyclic terpenoids and naphthoquinones were identified.The extract and fractions showed good antibacterial activity against periodontal pathogenic and cariogenic bacteria, which can be explained by the present compounds and showed low cytotoxicity to human cells. These data are relevant and encourage further research with this plant species, which can contribute to the discovery of new herbal medicines in order to help reduce these oral health problems.